The critical current densities of some Tl-based superconductors: Influence of the various atomic compositions - Kilic, A; Senoussi, S; Traxler, H; Moore, J; Collier, A; Goringe, M; Grovenor, C (1995)
We investigate the correlation between the critical current density and the critical temperatures of five Tl-based superconductors with T-c varying from 88 to 115 K. We find that for some of the samples J(c) is as high as 10(7)A/cm(2) at T = 4.2 K and H = 0. Perhaps, much more interestingly, for our best samples J(c)(H=0) exceeds 10(5)A/cm(2) at 100 K. It is also very important to emphasize that, contrary to Bi-based materials, the critical current density is not very sensitive to the magnetic field here. For instance, at T = 77 K and H = 20 kG, J(c) is still as high as 2x10(4)A/cm(2) while it is virtually zero in Bi-based systems.